Determinasi Penghindaran Pajak pada Perusahaan Manufaktur di Indonesia: Peran Profitabilitas, Leverage, Likuiditas dan Financial Distress sebagai Variabel Moderasi - Nabila Nurdiana Sukma; Intan Kurnia Permatasari (Universitas 45 Surabaya, 2026)
This study aims to analyze the effect of profitability, leverage, and liquidity on tax avoidance, with financial distress as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study uses secondary data obtained from the companies' annual financial reports. The sampling technique used was purposive sampling, with a sample size of 50 companies that met the criteria. Data analysis was performed using moderated multiple linear regression with the help of E-Views 12 software. The results show that profitability and liquidity have no effect on tax avoidance, while leverage and company size, as interaction variables, do. Financial distress weakens the effect of profitability, liquidity, and company size on tax avoidance, but strengthens the effect of leverage on tax avoidance. This research is expected to contribute to companies, investors, and the government in understanding the factors influencing tax avoidance practices and encouraging better tax transparency and compliance in the manufacturing sector.